Allergic proctocolitis: the clinical evolution of a transitory disease with a familial trend. Case reports - Fagundes-Neto,Ulysses (2013)
Allergic colitis is a clinical manifestation of food allergy during the first months of life. It is estimated that genetic factors play a role in the expression of this allergic disease. This case report described the clinical progress of infants who were cousins from two distinct family groups with allergic colitis. Five infants under six months of age and of both sexes were studied, with a diagnosis of allergic colitis characterized clinically and histologically by (1) rectal bleeding; (2) exclusion of infectious causes of colitis; (3) disappearance of symptoms after elimination of cow's milk and dairy products from the child's and/or the mother's diet. Patients were submitted to the following diagnostic investigation: complete blood count; stool culture; parasitologic examination of stools; rectoscopy or colonoscopy; and rectal biopsy. Patient age varied from 40 days to six months; three were males. All patients presented with complaints of intense colic and rectal bleeding. The colonoscopy showed presence of hyperemia of the mucosa with microerosions and spontaneous bleeding upon the procedure. Microscopy revealed the existence of colitis with eosinophilia >20 e/HPF. Patients were treated with a hypoallergenic formula and showed remission of symptoms. After one year of age, all were submitted to an oral challenge with a milk formula and presented food tolerance. Allergic colitis is a disease with evident genetic inheritance and a temporary character.